2022
DOI: 10.1161/circimaging.121.013477
|View full text |Cite
|
Sign up to set email alerts
|

Role of Echocardiography for Assessment of Cardiac Remodeling in Congenitally Corrected Transposition of Great Arteries

Abstract: Background: The purpose of this study was to assess the role of echocardiography for a comprehensive assessment of cardiac remodeling, and the relationship between indices of cardiac remodeling and cardiovascular events (defined as the composite end point of heart failure hospitalization, heart transplant, or cardiovascular death) in adults with congenitally corrected transposition of great arteries (cc-TGA). Methods: This is a retrospective study of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Most of the literature on risk stratification in adults with CHD was based on studies conducted in patients with specific CHD lesions, and these studies have identified risk factors such as systemic ventricular dysfunction, nonsystemic ventricular dysfunction, atrial fibrillation, impaired aerobic capacity, and prior heart failure hospitalization. 13,[22][23][24][25] Other studies that reported nonlesion risk 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the literature on risk stratification in adults with CHD was based on studies conducted in patients with specific CHD lesions, and these studies have identified risk factors such as systemic ventricular dysfunction, nonsystemic ventricular dysfunction, atrial fibrillation, impaired aerobic capacity, and prior heart failure hospitalization. 13,[22][23][24][25] Other studies that reported nonlesion risk 5.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature on risk stratification in adults with CHD was based on studies conducted in patients with specific CHD lesions, and these studies have identified risk factors such as systemic ventricular dysfunction, nonsystemic ventricular dysfunction, atrial fibrillation, impaired aerobic capacity, and prior heart failure hospitalization. 13,22–25 Other studies that reported nonlesion risk scores such as the perioperative adult CHD score and the Aristotle score focused on perioperative risk assessment and hence not applicable for risk assessment in ambulatory patients. 26,27 The Seattle heart failure model is a well-validated risk model in patients with acquired heart disease, but its prognostic role in adults with CHD is not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedural details for speckle tracking strain imaging for the assessment of RA, RV, LA, and LV function at this institution have been described. 15,16 RA and RV function were assessed using speckle tracking strain imaging obtained using Vivid E9 and E95 (General Electric Co, Fairfield, Connecticut) with M5S and M5Sc-D transducers (1.5-4.6 MHz) at frame rate of 40 to 80 Hz. Three-beat cine-loop clips were obtained from RV-focused apical four-chamber views.…”
Section: Echocardiographymentioning
confidence: 99%
“…In this issue, Egbe et al use a comprehensive echocardiographic protocol to study the impact of cardiac remodeling and chamber function on clinical outcomes. 5 The authors performed a baseline echocardiogram in adult ccTGA patients with a median age of 40 years and assessed clinical outcomes with a median follow-up time of around 9 years. It is a large single-center retrospective cohort study including 233 patients with 55% having simple ccTGA without other significant lesions.…”
mentioning
confidence: 99%